2020
DOI: 10.1186/s12875-020-01237-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of infection in asplenic adult patients by general practitioners in France between 2013 and 2016

Abstract: Background Guidelines that detail preventive measures against Streptococcus pneumoniae , Neisseria meningitidis , Haemophilus influenzae type b, and influenza are published annually in France to decrease the risk of severe infections in immunocompromised patients. We aimed at describing adherence to these guidelines by GPs in the management of their asplenic patients in France between 2013 and 2016. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Currently, the lack of recommendations by GPs and the absence of a clear communication circuit between GPs and branch specialists are considered the main obstacles to these patients’ access to immunisation. A 2020 French study 21 reported low VCs in a sample of 103 patients splenectomised from 2013 to 2016, concluding that the role of GPs is central in the long-term monitoring and management of infections in this population of patients, in collaboration with all healthcare professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the lack of recommendations by GPs and the absence of a clear communication circuit between GPs and branch specialists are considered the main obstacles to these patients’ access to immunisation. A 2020 French study 21 reported low VCs in a sample of 103 patients splenectomised from 2013 to 2016, concluding that the role of GPs is central in the long-term monitoring and management of infections in this population of patients, in collaboration with all healthcare professionals.…”
Section: Discussionmentioning
confidence: 99%
“…In France, national guidelines are published annually. Adherence by general practitioners was assessed in three hospitals and found to be insufficient 42 . Pneumococcal and meningococcal vaccine uptake was only 57%, with 74% uptake against Hib and 59% against influenza, with only 24% receiving all four vaccines.…”
Section: Education and Informationmentioning
confidence: 99%